Vaginal dehydroepiandrosterone compared to other methods of treating vaginal and vulvar atrophy associated with menopause - Pięta, Wojciech; Smolarczyk, Roman (Menopause Review/Przegląd Menopauzalny, 2020)
During the menopause, a fall in estrogen levels often leads to many unfavorable symptoms, including changes in the vascular and urogenital systems, in mood, and sleep. The symptoms of vulvovaginal atrophy are especially troublesome for menopausal women. These symptoms not only disturb the sexual sphere, but also functioning at work and in the family. Based on the literature, a review of contemporary methods of management in the case of symptoms of vulvar atrophy in menopausal women has been performed. The current methods of treating vulvovaginal atrophy in menopausal women are described. The pharmacology of the available dehydroepiandrosterone (DHEA) preparations, both oral and vaginal, was briefly analyzed. Own experiences of using DHEA are presented. Vaginal DHEA has been found to be an effective and safe treatment in menopausal women with symptoms of vaginal atrophy.